2022
DOI: 10.5713/ab.22.0150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium diacetate or microbial inoculants on aerobic stability of wilted rye silage

Abstract: Objective: The primary goal was to identify the effectiveness of chemical or biological additives in delaying the deterioration of early-harvested wilted rye silage after exposure to air. Methods:Rye harvested as a whole plant at the early heading stage was wilted for 24 h. The wilted forage was divided into treatments including sodium diacetate (SDA) at 3 (SDA3) and 6 g/kg (SDA6), Lactobacillus plantarum (LP), L. buchneri (LB), or their equal mixture (LP + LB) at 1 × 10 6 cfu/g fresh matter.Results: After 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Knický and Spörndly [14] reported that potassium sorbate was effective in inhibiting yeasts, molds, and spore-forming bacteria. Sodium diacetate can ionize into acetic acid easily, suppressing the activity and growth of harmful microorganisms during ensiling [15]. Okur et al [16] also found the aerobic stability of maize silage treated with sodium diacetate was much improved after exposure to air.…”
Section: Introductionmentioning
confidence: 99%
“…Knický and Spörndly [14] reported that potassium sorbate was effective in inhibiting yeasts, molds, and spore-forming bacteria. Sodium diacetate can ionize into acetic acid easily, suppressing the activity and growth of harmful microorganisms during ensiling [15]. Okur et al [16] also found the aerobic stability of maize silage treated with sodium diacetate was much improved after exposure to air.…”
Section: Introductionmentioning
confidence: 99%